Father Flanagan of Boys Town : a man of vision - Reilly, Hugh J.; Warneke, Kevin (Boys Town, Neb. : Boys Town Press, 2008)
"This is the tale of Edward Flanagan, a young Irish lad shepherding a flock of sheep on a farm in Ballymoe, who became the famed Father Flanagan, founder of America's Boy Town, guardian of thousands of orphaned, neglected, and abandoned boys, and advisor to presidents. From a large Irish family, Flanagan suffered through ill health and setbacks to pursue his desire to join the priesthood. Following his older brother and fellow priest to the plains of Nebraska, he served several parishes and opened a hotel for homeless men before finding his life's mission to care for and give a voice to young boys whom society had despaired of and cast aside" --Cover, p. 4.
Prologue. Their only hope -- 1. The boy from Ballymoe -- 2. Preparing to do God's work -- 3. Inspired by a boy who needed a home -- 4. Finding a home -- 5. Building a village for little man -- 6. Putting boys town on the map -- 7. Welcoming Hollywood -- 8. America's No. 1 war dad -- 9. Helping the children of defeat -- 10. His work continues -- Afterword: By Father Clifford Stevens.
Includes bibliographical references (p. 179-196).
Keywords: Flanagan, Edward Joseph, -- 1886-1948.; Father Flanagan's Boys' Home; Social workers -- United States -- Biography; Problem children -- Institutional care -- United States -- History